Universities at the crossroads - Beteille,Andre (New Delhi Oxford University Press, 2010)
Drawing from several decades of scholarship, these essays astutely examine a largely undocumented institution-the university in India. By focusing on the academic, social, and political pressures that impinge on this institution, the book also boldly addresses the much-debated issue of reservations in the country.
Includes index
Keywords: Education, Higher -- India; Higher education and state -- India